Whom Do Chief Ministers Serve? - Brian Min; Yogesh Uppal; Rangamohan Eunni (Public Finance Review, 2026)
Chief ministers in India play among the most important roles in determining access to a wide range of public services. Do chief ministers use the power of their office to enhance public service delivery broadly across the states in which they govern? Or do they more narrowly direct resources towards the individual constituencies they represent and in which they must seek re-election? Using a geographical proximity design, we examine new data covering 1992 to 2012 to study the impact of chief minister representation on a constituency’s access to electricity and find clear variations in distribution strategies across states. We find that chief ministers target their constituencies with increases in electricity supply. These variations in public service targeting are driven by differences in institutional environment and political security of India’s chief ministers. We also find some evidence of short-term positive spillovers in the local region.